Sweet enemy : a veiled seduction novel - Snow, Heather (New York : Signet Eclipse, 2012)
Believing that the Earl of Stratford's father is responsible for her own father's murder, Miss Liliana Clarement arrives at the Earl's family estate, posing as a husband hunter, to find the truth, but instead finds love in the arms of the enemy.
Includes excerpt from: Sweet deception (p. [365]-377).
Keywords: Man-woman relationships -- Fiction; Nobility -- England -- Fiction; Love stories; Historical fiction; Regency fiction